The Effect of Applying Sanctions and Rewards on Teacher’s Performance Motivation - Yunidar, Yunidar; Ahyani, Nur; Wachidi, Achmad (Journal of Social Work and Science Education, 2024)
This study aims to find out the influence of awarding policies (reward) and legal sanctions (punishment) to Civil Servants in the Department of Education and Culture of Central Bangka Regency. The research method that the authors used in this study was a survey research method with data collection techniques through observation, interviews, questionnaires, and documentation studies. The population in this study is 157 teachers and employees in Cluster 1, Koba District, Central Bangka. Samples were carried out using Bivariate Pearson. The validity test analysis uses factor validity and item validity, while the reliability test uses the SPSS program. To get a sample that can describe the population, in determining the research sample used the Slovin Formula as many as 52 teachers and employees in Cluster 1, Koba District, Central Bangka Regency. Based on the results of the analysis, an r count of 0.981 is obtained, meaning that 98% of the variation in changes in employee performance (Y) is caused by reward (X1) and punishment (X2) factors. While the remaining 2% variation or employee performance is caused by other variables not included in this study. The reward variable (X1) partially has a significant effect on employee performance (Y) and punishment (X2) partially has no significant effect on employee performance (Y). So, rewards have the most dominant effect on the performance of teachers and employees in Cluster 1, Koba Bangka Tengah District.